"I Feel I'm in Best Hands with You!": A Survey of Patient Satisfaction in a German University Skin Cancer Centre - Steeb, Theresa; Wessely, Anja; Merkl, Heike; Kirchberger, Michael; Bosch-Voskens, Caroline; Erdmann, Michael; Heinzerling, Lucie; Berking, Carola; Heppt, Markus (Acta Dermato-Venereologica, 2021)
An important measure of hospital quality is the satisfaction of patients. The aim of this cross-sectional study, performed in the dermato-oncology unit of the university hospital in Erlangen, Germany, was to assess skin cancer patients' degree of satisfaction with healthcare services. Self-administered questionnaires on patient satisfaction regarding contact with staff, need for information, and recommendation of the skin cancer centre were distributed in the day-care unit and the outpatient department to patients between April and June 2017. Results were reported descriptively and subgroup differences were explored using the Mann-Whitney U test, binary logistic regression, or χ2 test. Overall, 496 of 571 questionnaires were returned (86.9%). The median of all satisfaction items ranged between 1 (very good) and 2 (good). The majority of patients wanted more detailed information about skin cancer (46.7%, 142/304). Long waiting times were often criticized (22.8%; 80/351). Particular attention in addressing specific needs and fears may further increase patient satisfaction.
CRIS-Team Scopus Importer:2021-08-13
Keywords: cross-sectional study; melanoma; quality improvement; quality of care; skin cancer; patient satisfaction